(untitled) (International Journal of Mathematics and Physics, 2013)
The obtained results continue our work on the optical properties of Kelbg-pseudopotential-modelled plasmas [1]. Since the difficulty of the uncertainty in the determination of the Nevanlinna parameter function is overcome by developing a regular method for deriving the Nevanlinna parameter function which essentially stems from the asymptotic behavior of the simulated dynamic collision frequency in the classical method of moments, it is possible, on the basis of the dynamic collision frequency (DCF) of hydrogen-like plasmas to derive the dynamic conductivities. Here internal and external dynamic conductivities, i.e. their imaginary and real parts are presented. Some information on the method of moments (MM) is provided.